Predictability of the Global Limb Anatomic Staging System (GLASS) for Technical and Limb Related Outcomes: A Systematic Review and Meta-Analysis. (July 2022) - Shirasu, Takuro; Takagi, Hisato; Gregg, Alexander; Kuno, Toshiki; Yasuhara, Jun; Kent, K. Craig; Clouse, W. Darrin
Abstract : Objective: The newly proposed Global Limb Anatomic Staging System (GLASS), a categorical staging of infrainguinal artery disease complexity, is expected to correlate with clinical outcomes in patients with chronic limb threatening ischaemia (CLTI). This study aimed to verify the relationship between GLASS stages and clinical outcomes after endovascular treatment (EVT) and bypass surgery (BS). Data Sources: MEDLINE, Web of Science Core Collection, and Google Scholar were searched in consultation with a health sciences librarian through June 2021. Review Methods: This systematic review and meta-analysis was carried out according to the PRISMA guidelines. All studies comparing the outcomes of patients with CLTI stratified by GLASS staging were eligible. Amputation free survival (AFS), limb salvage rate (LSR), major adverse limb event (MALE), overall survival, immediate technical failure (ITF), and limb based patency (LBP) were analysed. Data were pooled and synthesised with a random effects model. Results: Datasets from seven retrospective cohort studies and one randomised control trial with a total of 2 204 patients (2 483 limbs) were identified. Pooled estimates demonstrated statistical differences between GLASS 1+2 and GLASS 3 in LSR (HR 0.61; 95% CI 0.47 – 0.80, p < .001) and MALE (HR 0.66; 95% CI 0.53 – 0.83, p < .001). After stratification, there were statistical differences in AFS, LSR, and MALE between GLASS 1+2 and GLASS 3 in the EVT subgroup but not in BS. In GLASS 2 and 3, MALE was significantly worse after EVT. In GLASS stages 1, 2, and 3, ITF after EVT was 3.9%, 5.3%, and 27.9%, respectively. LBP after EVT was significantly different between GLASS 1+2 and GLASS 3 (HR 0.83; 95% CI 0.71 – 0.97, p  = .020). Conclusion: GLASS is predictive of LSR and MALE as well as ITF and LBP after EVT. The current meta-analysis suggests advanced GLASS stages favour BS over EVT.